2016
DOI: 10.1080/2162402x.2016.1149673
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of RIP3 and MLKL to immunogenic cell death signaling in cancer chemotherapy

Abstract: Chemotherapy can reinstate anticancer immunosurveillance through inducing tumor immunogenic cell death (ICD). Here, we show that anthracyclines and oxaliplatin can trigger necroptosis in murine cancer cell lines expressing receptor-interacting serine-threonine kinase 3 (RIP3) and mixed lineage kinase domain-like (MLKL). Necroptotic cells featured biochemical hallmarks of ICD and stimulated anticancer immune responses in vivo. Chemotherapy normally killed Rip3 ¡/¡ and Mlkl ¡/¡ tumor cells and normally induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(157 citation statements)
references
References 64 publications
4
145
1
2
Order By: Relevance
“…NIH-3T3 mouse fibroblasts driven into necroptosis through a dimerizable variant of Ripk3, as well as TC-1 mouse lung carcinoma and EL4 mouse lymphoma cells responding to TNF plus SMAC mimetics and Z-VAD-fmk (TSZ), expose or secrete several DAMPs that are involved in anticancer immunosurveillance, including, but perhaps not limited to, calreticulin (CALR), ATP, and high mobility group box 1 (HMGB1) (126, 188). Accordingly, the coincubation of necroptotic NIH-3T3 cells with bone marrow–derived DCs promotes the maturation of the latter, as assessed by Cd86 and MHC class II surface staining (126).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
See 2 more Smart Citations
“…NIH-3T3 mouse fibroblasts driven into necroptosis through a dimerizable variant of Ripk3, as well as TC-1 mouse lung carcinoma and EL4 mouse lymphoma cells responding to TNF plus SMAC mimetics and Z-VAD-fmk (TSZ), expose or secrete several DAMPs that are involved in anticancer immunosurveillance, including, but perhaps not limited to, calreticulin (CALR), ATP, and high mobility group box 1 (HMGB1) (126, 188). Accordingly, the coincubation of necroptotic NIH-3T3 cells with bone marrow–derived DCs promotes the maturation of the latter, as assessed by Cd86 and MHC class II surface staining (126).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
“…In this model, the Ripk3-driven Ripk1-mediated activation of NF-κB is crucial for the elicitation of optimal antitumor immunity (126). The subcutaneous delivery of TC-1 cells treated with TSZ to syngeneic mice also results in virtually complete protection against the subsequent inoculation of living cancer cells of the same type, as does this administration of TC-1 cells succumbing to the canonical immunogenic cell death (ICD) inducer mitoxantrone (MTX) (188). Only WT TC-11 cells treated with MTX induce such a protective anticancer immune response, whereas Ripk3 −/− or Mlkl −/− TC-1 cells fail to do so (188).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…97 Such a chemokine mixture is particularly efficient at recruiting neutrophils towards the dying cells (a process that appears to be evolutionarily conserved), paving the way to the CALR-dependent phagocytosis of dying cancer cells or corpses thereof, and the cytotoxic targeting of residual malignant cells. 97 We characterized a naturally-occurring preclinical model of cancer that exhibits intrinsic resistance against mitoxantrone-induced ICD in vivo secondary to a defect in CALR exposure, 199 and we documented that anthracyclines and oxaliplatin can trigger a necroptotic variant of ICD [211][212][213][214][215] in cancer cells expressing receptor interacting serine/threonine kinase 3 (RIP3K) and the pseudokinase mixed lineage kinase domain-like (MLKL). 215 Finally, we found that an engineered oncolytic vaccinia virus 216 can induce ICDdependent antitumor immunity, which can be further potentiated by the co-administration of ICD-inducing chemotherapy or immune checkpoint blockers (ICBs), 216 and that pharmacological inhibition of signal transducer and activator of transcription 3 (STAT3) 217 signaling boosts the therapeutic efficacy of anthracyclines upon increased type I interferon (IFN) secretion.…”
Section: Recent Preclinical Developmentsmentioning
confidence: 99%
“…97 We characterized a naturally-occurring preclinical model of cancer that exhibits intrinsic resistance against mitoxantrone-induced ICD in vivo secondary to a defect in CALR exposure, 199 and we documented that anthracyclines and oxaliplatin can trigger a necroptotic variant of ICD [211][212][213][214][215] in cancer cells expressing receptor interacting serine/threonine kinase 3 (RIP3K) and the pseudokinase mixed lineage kinase domain-like (MLKL). 215 Finally, we found that an engineered oncolytic vaccinia virus 216 can induce ICDdependent antitumor immunity, which can be further potentiated by the co-administration of ICD-inducing chemotherapy or immune checkpoint blockers (ICBs), 216 and that pharmacological inhibition of signal transducer and activator of transcription 3 (STAT3) 217 signaling boosts the therapeutic efficacy of anthracyclines upon increased type I interferon (IFN) secretion. 217 Pfirschke and co-authors (from Massachusetts General Hospital Research Institute and Harvard Medical School, Boston, MA, USA) found that autochthonous tumors lacking tumorinfiltrating lymphocytes (TILs) can be sensitized to immunological rejection via a Toll-like receptor 4 (TLR4)-dependent mechanism when suitable ICD inducers like oxaliplatin or cyclophosphamide are combined with ICBs targeting programmed cell death 1 (PDCD1; best known as PD-1) 218 and/or cytotoxic T-lymphocyte associated protein 4 (CTLA4).…”
Section: Recent Preclinical Developmentsmentioning
confidence: 99%